2015
DOI: 10.3892/mmr.2015.3340
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine gland-derived vascular endothelial growth factor modulates proliferation, apoptosis and migration in pancreatic cancer cells

Abstract: Endocrine gland‑derived vascular endothelial growth factor (EG‑VEGF) is a newly cloned factor that selectively acts on the endothelium of endocrine gland cells. EG‑VEGF was previously identified as an important cytokine, involved in the modulation of apoptosis in pancreatic cancer cell lines. The present study examined the effects of EG‑VEGF proliferation and migration, in pancreatic cancer cells. To determine the potential for EG‑VEGF as a therapeutic target for pancreatic cancer, the expression of EG‑VEGF we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…PROK-1 is secreted by cells in the placenta that promotes angiogenesis and capillary fenestration only in endocrine glands 27 28. Data from in vitro studies using normal and tumor cells show that PROK-1 and its receptor are present within the pancreas, which can stimulate proliferation and reduce apoptosis of endothelial cells 29 30. It was interesting that both IL-6 and GCG were elevated during later gestational ages, as animal studies have provided insights to the relationship between IL-6, GCG, and insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…PROK-1 is secreted by cells in the placenta that promotes angiogenesis and capillary fenestration only in endocrine glands 27 28. Data from in vitro studies using normal and tumor cells show that PROK-1 and its receptor are present within the pancreas, which can stimulate proliferation and reduce apoptosis of endothelial cells 29 30. It was interesting that both IL-6 and GCG were elevated during later gestational ages, as animal studies have provided insights to the relationship between IL-6, GCG, and insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PROK1 was shown to be up-regulated in several types of cancers, such as colorectal cancer, pancreatic cancer, prostate cancer, and ovarian cancer [ 25 , 26 , 27 , 28 , 29 , 30 ], and was regarded as a poor prognostic marker and survival factor. These PROK1-related malignancies were closely associated with advanced clinical stage, histological grade, and distant metastasis, which may probably through regulating peritumoral angiogenesis or/and strengthened cancer cell invasiveness [ 25 , 26 , 27 , 28 , 29 , 30 ]. The PROK1-overexpressing cells in the present study could be a mimicking condition of malignancy, and the increased cell invasion ability suggested the potential role of PROK1 in cancer biology.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it has been shown that the PKS is associated with malignant carcinoma development [36]. In detail, PK1, an already known angiogenic factor, has been associated with tumorigenesis, cellular invasion, and metastases onset in several tumors [75][76][77][78], including CRC [65,79]. From these studies, which analyzed PK1 expression in human colorectal cancer tissue samples, it emerged that PK1 upregulation was present in about 40% of the CRC samples collected.…”
Section: Evidence Of the Pks In Gastrointestinal Tumorigenesis In Ibdsmentioning
confidence: 99%